2000
DOI: 10.1111/1468-0335.00198
|View full text |Cite
|
Sign up to set email alerts
|

Road Accidents and Traffic Flows: An Econometric Investigation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 16 publications
7
38
1
Order By: Relevance
“…Newberry (1988) and Vitalino and Held (1991) find nearly proportional patterns, while and Martin (2002) show parabolic functional relationships. Dickerson et al (2000) also confirmed a non-linear pattern, revealing that the nearlyproportional relationship may be erroneous since it may result from the aggregation of heterogeneous accident-flow relationships which do not exhibit proportionality. In particular, the magnitude of accident externality varies between road classifications and geographical areas.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Newberry (1988) and Vitalino and Held (1991) find nearly proportional patterns, while and Martin (2002) show parabolic functional relationships. Dickerson et al (2000) also confirmed a non-linear pattern, revealing that the nearlyproportional relationship may be erroneous since it may result from the aggregation of heterogeneous accident-flow relationships which do not exhibit proportionality. In particular, the magnitude of accident externality varies between road classifications and geographical areas.…”
mentioning
confidence: 69%
“…1 Some recent works also show how accidents increase with congestion cuts, emerging a trade-off between both externalities Dickerson et al, 2000;Martin, 2002;Noland and Quddus, 2005). However, toll setting in practice has been usually decided to fight congestion and funding infrastructure without taking into account road safety outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these have examined the role of speed or traffic flow on the probability of an accident or traffic fatality and are useful in calculating road user charges (Golob, Recker, and Alvarez, (in press); Dickerson, Peirson and Vickerman, 2000;Shefer and Rietveld, 1997;Vitaliano and Held, 1991). Other studies (mostly appearing in the transport engineering literature) examine the impact of road environment conditions (roadway design and weather) on accident rates and severity (Milton and Mannering, 1998).…”
Section: Micro-level Studies Of the Causes Of Accidents Or Fatalitiesmentioning
confidence: 99%
“…Research undertaken by Dickerson et al (2000) investigated the relationship between the frequency of road crashes and traffic flow with the aim of estimating the change in the external cost of crashes caused by additional traffic flow. Different road types and geographical areas were considered and they found that a strong negative crash externality was associated with high traffic flows.…”
Section: Introductionmentioning
confidence: 99%